The learning strategy for biodiversity concept: Pedagogical analysis based on technological pedagogical and content knowledge - Umar, Mohammad Farhan; Bariroh, Ghurrotul; Jannah, Novi Dewi Khadikatul; Rahmat, Adi; Riandi, Riandi (STKIP Persada Khatulistiwa Sintang, 2024)
Sustainable Development Goals (SDGs) emphasize quality education and environmental protection. Biodiversity education in Phase E requires students to solve problems related to biodiversity. However, complex terminology and limited learning tools create challenges. This research aims to analyze effective learning strategies for teaching biodiversity using a TPACK framework. The method used in this research is a literature review carried out systematically by PRISMA. The analysis will map pedagogical approaches, content based on CoRes analysis, and technological aspects. Findings will inform the development of effective learning strategies for high school biodiversity education, contributing to achieving SDGs, particularly SDG 15 on terrestrial ecosystems. The finding shows that The use of CoRes to narrow down the information is required to instruct students and promote the attainment of the 15th SDG goal. Based on the findings of the analysis, the pedagogical review of the approach used, namely local wisdom, the field trip method, and the discovery learning model, as well as the use of technology to assist students in identifying PlantNet, Picture This, and iNaturalist, is considered effective to be implemented in learning biodiversity material.